2021
DOI: 10.3390/nu13072386
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Mineral Density and Risk for Osteoporotic Fractures in Patients with Chronic Pancreatitis

Abstract: Introduction: Chronic pancreatitis (CP) can lead to malnutrition, an established risk factor for low bone mineral density (BMD) and fractures. This study aims to determine the prevalence of low BMD, assess fracture incidence and explore risk factors for fractures in patients with CP. Patients and methods: We performed a retrospective analysis of all patients treated for CP at Karolinska University Hospital between January 1999 and December 2020. Electronic medical records were retrieved to assess demographic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
18
0
3
Order By: Relevance
“…Thus, the predictive factors for fracture risk and osteoporosis have been investigated by many researchers. Low BMD has been reported to be associated with aging, low body weight, physical inactivity, smoking, excessive alcohol consumption, diabetes, dyslipidemia, and pernicious anemia [5][6][7]. In addition, chronic iron-deficiency anemia has been suggested to induce bone resorption and increase the risk of osteoporosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the predictive factors for fracture risk and osteoporosis have been investigated by many researchers. Low BMD has been reported to be associated with aging, low body weight, physical inactivity, smoking, excessive alcohol consumption, diabetes, dyslipidemia, and pernicious anemia [5][6][7]. In addition, chronic iron-deficiency anemia has been suggested to induce bone resorption and increase the risk of osteoporosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A , E and K are reduced in fat malabsorption and can be used to monitor malnutrition in PEI due to CP 47 . Osteoporosis because of malnutrition in PEI can be monitored by bone density measurements, as recommended in the UEG guidelines 25 . Al these parameters were not available.…”
Section: Discussionmentioning
confidence: 99%
“…It is notoriously underdiagnosed and undertreated. Since the consequences due to the resulting malnutrition can be severe, such as osteoporosis 25 and cardiovascular events, 26 adequate pancreatic enzyme replacement therapy (PERT) is pivotal and emphasized by the guidelines. 11 In this large cross‐sectional study, we found variable adherence to the recommendations of PERT from the UEG guidelines in this large cohort from dedicated specialist centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many medicines are used to treat osteoporosis and repair the bone tissue by alleviating the expression of tissue inflammatory factors [33][34][35]. Meanwhile, inflammatory factors infiltration caused by many inflammatory diseases can also lead to abnormal bone metabolism, resulting in increased fracture probability, such as chronic pancreatitis [36,37], chronic enteritis [38], hepatitis [39], and chronic obstructive pulmonary disease [40]. IL-6 is a common inflammatory factor whose effect on bone metabolism has been confirmed already [41].…”
Section: Discussionmentioning
confidence: 99%